THE PECULIAR PROPERTIES OF A POLYSEMANTIC WORD IN THE TELEUT LANGUAGE - O. A. Bulgakova (Вестник Кемеровского государственного университета, 2015)
The article is devoted to the study of ambiguity in the non-literate language of the minority indigenous people of the North Teleuts living on theterritoryofKemerovoregion. The aim is to describe the specifics of the ways of polysemy development in the Teleut language through the specifics of the worldview and world perception of the ethnic group, which is reflected in categorizational activity of the mind. Polysemantic word is considered as a complex cognitive structure resulting from the classifying, or categorizational, activity of the mind. The prototypical nature of the conceptual category determines the semantic variability of a word, its ability to be applied to a wide range of referents. Such property of the prototypical category as openness, willingness to accept new members, quite remote in character and properties from the prototype, allows to understand the reason for the semantic variability of words, as well as their ability to a high degree of polysemy, and to identify the peculiarities of nomination in the Teleut language which determines the development of polysemy through the implementation of propositional structures, characteristic of the linguistic worldview of the Teleuts.